Effect of hydrocooling, packaging, and cold storage on the post-harvest quality of peppermint (Mentha piperita L.) - C.K.R. BARBOSA; M.C.M. FONSECA; T.P. SILVA; F.L. FINGER; V.W.D. CASALI; P.R. CECON (Universidade Estadual Paulista, 2016)
ABSTRACT The purpose of this study was to assess the effects of hydrocooling and polyethylene terephthalate (PET) perforated and non-perforated packaging on post-harvest quality of peppermint (Mentha piperita L.) leaves stored at 5 and 25ºC. The experiments were conducted using a subdivided parcel layout in a completely randomized design with four replicates. Each parcel used a 2x3 layout (two hydrocooling treatments and three packaging treatments) with subparcels for storage time. The shelf life, chlorophyll content, mass loss (ML), relative water content (RWC), total soluble sugars (TSS), reducing sugars (Red), non-reducing sugars (NRed) and starch of the leaves were determined. Cold storage increased the shelf life of the peppermint by up to 64 times (>15 days). Hydrocooling increased the RWC of the leaves. Plastic packaging was effective in maintaining the RWC. Unperforated packages more effectively prevented ML in the peppermint leaves and prevented the leaves from wilting for a longer period of time. The chlorophyll content of the leaves varied according to the treatment. The soluble sugars and starch levels varied according to RWC. Hydrocooling with the use of non-perforated plastic packages was the most effective method for maintaining the postharvest quality of the peppermint.